Psychometric properties of the health literacy instrument in Brazil (HLS-EU-BR47) - Luis Saboga-Nunes; Uwe H. Bittlingmayer; Stefanie Harsch; Silvana Ligia Vincenzi; Silvio Aparecido da Silva; Andréa Cristina Konrath; Lizandra Brasil Estabel; Eliane Lourdes da Silva Moro; Luciane Alves Santini; Filipe Xerxeneski da Silveira; Darclé Cardoso; Roselita Sebold; et al. (BMC, 2024)
Abstract Background Health literacy (HL) is a key component of health promotion and sustainability and contributes to well-being. Despite its global relevance, HL is an under-researched topic in South America but is now debuting its exploration in Brazil. To leverage its benefits for South America, the mere translation of validated tools into Portuguese is insufficient. Rather, it is necessary to examine their validity. This study aims to assess the psychometric properties of the European Health Literacy Questionnaire (HLS-EU-BR47) using the Item Response Theory (IRT) in a population-based sample of adults in Brazil. Methods A cross-sectional online study was conducted across Brazil and included 1028 participants aged 18 years and above (80% women). Cronbach's alpha, McDonald's omega, factor analysis, graded responses model, Item Characteristic Curve, HL levels based on this, HL standard calculation, IRT, and regular score correlation were computed. Results The instrument exhibit high reliability (Cronbach's alpha 0.95). Factor analysis yielded one factor. IRT was appropriate for data analysis because it allowed quality evaluation of items and constructed a scale to quantify HL. The 47 items and latent features of respondents in the same unit of measurement are positioned in the construction of the HLS-EU-BR47 instrument. The percentages of individuals at each HL level, calculated using IRT, were found to be comparable to those obtained through the standard computation, e.g., 3.2% of people reported very low HL versus 10.8% inadequate HL, 56.2% reported low HL versus 39.5% problematic HL, 31.1% had moderate HL versus 30.1% sufficient HL, and 9.5% had high HL versus 19.7% with excellent HL. The mean HL scores were comparable between women and men (33.9 vs. 33.7, P = 0.36). Conclusion This study provides new evidence of the validity of a widely used HL instrument for the population of South America (in this case, Brazil). This tool can be utilized by citizens, health professionals, and regional/national policymakers to inform the development of initiatives to assess and improve the HL of individuals, groups, and communities. Further studies are needed to confirm and extend the findings and to explore the influence of local cultures and practices in the vast Brazilian territory on HL.